Community-based stroke system of care improves patient outcomes in Chinese rural areas. Issue 7 (7th March 2018) - He, Mingli; Wang, Jin'e; Dong, Qing; Ji, Niu; Meng, Pin; Liu, Na; Geng, Shan; Qin, Sizhou; Xu, Wenyan; Zhang, Chuantong; Li, Dabo; Zhang, Huamin; et al.
Abstract : Background: Building effective and efficient stroke care systems is a key step in improving prevention, treatment and rehabilitation of stroke. The aim of this study was to evaluate the effectiveness of this stroke system of care on stroke management during a 2-year follow-up. Methods: A stroke system of care was developed from November 2009 to November 2010 in three townships in Ganyu County. Additional three matched townships were invited as controls. We first investigated the stroke incidence of these populations. Subsequently, this stroke system of care and an educational campaign in the three intervention townships were implemented and the effectiveness of the system was evaluated in the next 2 years. Results: At postintervention, more patients in the intervention communities obtained stroke knowledge and then the proportion of patients with stroke who were admitted within 3 hours of onset markedly increased in 2012 (12.0% vs 8.1%, p=0.044) and in 2013 (15.2% vs 9.7%, p=0.008) compared with those in the control communities. In the intervention communities, this proportion of patients with acute ischaemic stroke who received thrombolytic treatment was markedly raised from 2.1% in 2012 to 3.0% in 2013. More importantly, the fatality rate substantially decreased in 2013 in the intervention communities compared with that in the control communities (6.1% vs 9.7%, p=0.032). Similarly, the disability rate significantly decreased in 2013 (45.3% vs 51.5%, p=0.045). Conclusions: The community-based stroke system of care was effective and practical for optimising stroke treatments and improving patient outcomes. Trial registration number: ChiCTR-RCH-13003408, Post-results.